Doctor Who. The complete eighth series [videorecording (Blu-Ray)]. - Smith, Matt, 1982-; Capaldi, Peter; Coleman, Jenna, 1986- (BBC Worldwide, 2014)
The Doctor is back! This time with a new face, a new personality, and a new set of thrilling adventures across time and space.